Genome-wide identification and characterization of NLR genes in lamprey (Lethenteron reissneri) and their responses to lipopolysaccharide/poly(I:C) challenge. (March 2022) - Hui, Fan; Guo, Siqi; Liu, Jinzhao; Li, Meiao; Geng, Ming; Xia, Yimeng; Liu, Xin; Li, Qingwei; Li, Jun; Zhu, Ting
Abstract: The nucleotide oligomerization domain (NOD)-like receptor (NLR) is a relatively conserved receptor family involved in natural immunity that plays a key role in the resistance to pathogen invasion and regulation of the innate immune response. Lethenteron reissneri (lamprey) is a representative species of existing ancient jawless vertebrates. Studies of the evolutionary relationship of immune system-related molecules in lampreys can provide an important reference for the origin and evolution of innate immunity. However, the characterization and evolutionary patterns of the NLR family remain unclear in the lamprey genome. Based on the genome database of L. reissneri, we identified nine NLR genes, characterized their functional domains and chromosomal positions, and constructed a network comprising the results of gene structure and gene-collinearity analyses. Comparative genomics studies suggest that Lr-NODa and Lr-NODb most likely share the common ancestor of NOD1 and NOD2 in jawed vertebrates, and that Lr-NODb may have been generated by lamprey-specific tandem duplication of Lr-NODa . Additionally, phylogenetic analysis of the NLRC subfamily suggests that Lr-NLRC3a has ancestral traits and may be derived from the common ancestor of another vertebrate NLRC subfamily. Further analysis of the formation of the NLRC subfamily has shown that exon shuffling, domain recombination, and chromosome rearrangement play important roles in its structural evolution. Furthermore, real-time quantitative polymerase chain reaction shows that most NLR genes in lamprey are highly expressed in the immune tissues of the heart, gill, and supraneural body, with these genes also showing significant responses to polyinosinic-polycytidylic acid infection. These results indicate that NLR genes are involved in the immune protection of L. reissneri and provide an important theoretical foundation for studies of the functional evolution of vertebrate NLRs involved in the innate immune system. Highlights: Nine NLR genes were identified in the Lethenteron reissneri genome. The NLRs of L. reissneri were divided into two subfamilies: NLRA and NLRC. The number of NLRs in lamprey NLRs increased via tandem or dispersed duplications. NLRs underwent exon shuffling or chromosome rearrangement during evolution. NLRs were highly expressed in immune tissues and strongly responded to pathogen infection.